PENGARUH KEPEMIMPINAN, BUDAYA ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PDAM KABUPATEN KONAWE - Irham Natsir K (Jurnal Manajemen Lakidende: Economic & Business, 2019)
This study aims to analyze how much influence Leadership, Organizational Culture and Organizational Commitment on the performance of employees of Konawe Regency. Operationally the leadership variable is measured by four indicators, the organizational culture variable is measured by four indicators, the organizational commitment variable is measured by four indicators and the performance variable is measured by five indicators. The population in this study amounted to 45 employees of the Konawe District PDAM, with the sampling technique using saturated sample techniques. Data taken from questionnaires distributed to respondents. Analysis of the data used in this study are: multiple regression test, t test, F test, normality test and determinant coefficient test. The results showed that the results of the leadership t test on employee performance indicated by the Sig value of 0.042 smaller than 0.05, which means that the leadership variable had a significant effect on performance variables, organizational culture on employee performance obtained a Sig value of 0.11 smaller than 0 05, which means that organizational culture has a significant effect, organizational commitment to employee performance is indicated by the acquisition of a Sig of 0.018 less than 0.05, which means that organizational commitment has a significant effect on employee performance.